2021
DOI: 10.1016/j.ica.2020.119959
|View full text |Cite
|
Sign up to set email alerts
|

Divalent cobalt and copper coordination complexes of κ2-N, O-derivatives of (Z)-1-R-2-(2′-oxazolin-2′-yl)-eth-1-en-1-ates: Structure and reactivity patterns

Abstract: The synthesis and characterisation of a small library of Co and Cu derivatives (29 examples) incorporating the (Z)-1-R 1 -2-(4',4'-R 2 -2'-oxazolin-2'-yl)-eth-1-en-1-ate (L: R 1 = alkyl or aryl; R 2 = H or Me) skeleton is described. This work includes six new derivatives of "Tohda's Ligands". In the case where R 2 = H, solid-state stable Co(II) materials of formula Co(κ 2 -N,O-L)2 could, in some cases, be obtained following base-induced deprotonation of L+H and treatment with hydrated CoX2 salts. These complex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 112 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…The straightforward reaction of readily available cis-MoO 2 (acac) 2 to give the desired air-stable materials occurred in the absence of an added base, a situation that is typically required to produce reaction conditions necessary to coordinate the enolate fragment obtained from LH. Hence, these Mo 6+ -based materials formed more readily when compared to most of the Ni 2+ , Co 2+ , Cu 2+ , and Ir + complexes reported previously [9,[11][12][13]. Molecular modeling (Section 2.2) suggested that the likely ligand orientation around a mononuclear Mo 6+ center was that of isomer III (Scheme 3).…”
Section: Synthesis and Structural Investigationsmentioning
confidence: 83%
See 1 more Smart Citation
“…The straightforward reaction of readily available cis-MoO 2 (acac) 2 to give the desired air-stable materials occurred in the absence of an added base, a situation that is typically required to produce reaction conditions necessary to coordinate the enolate fragment obtained from LH. Hence, these Mo 6+ -based materials formed more readily when compared to most of the Ni 2+ , Co 2+ , Cu 2+ , and Ir + complexes reported previously [9,[11][12][13]. Molecular modeling (Section 2.2) suggested that the likely ligand orientation around a mononuclear Mo 6+ center was that of isomer III (Scheme 3).…”
Section: Synthesis and Structural Investigationsmentioning
confidence: 83%
“…Thus far, we have only observed the κ 2 -N,O bonding motif following formal H + loss from LH; hence, metal-bound enolate anions (L − ) are found within the metal coordination sphere. This has been shown in the chemistry of Co 2+/3+ , Cu 2+ [9,11], Ni 2+ [12], and Ir +/3+ [13], in addition to main group examples [14]. Herein, we detail our exploration into the reactivity of formally Mo 6+ metal centers with LH derivatives, as the reactivity of these compounds with Group 6 metals is currently completely unexplored.…”
Section: Introductionmentioning
confidence: 91%